Burnout Ditinjau dari Big Five Personality Traits pada Pegawai Puskemas - Fadhila A. Husain; Lenny Syamsuddin; Muhammad Mursyid (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2026)
High work demands among public health center employees and the scarcity of research on the Big Five Personality Traits and burnout within Indonesian primary healthcare motivated this study. The objective was to examine the relationship between the Big Five Personality Traits and burnout among employees at Telaga Public Health Center, Gorontalo Regency. A quantitative correlational design was utilized. The research population included 83 employees selected through total sampling, with a final sample of 62 respondents. Data collection employed the Big Five Inventory (BFI) and the Maslach-Trisni Burnout Inventory (M-TBI), and analysis was conducted using the Pearson Product-Moment correlation test in Jamovi. Results indicated a significant negative relationship between conscientiousness and burnout (r = - 0.314; p = 0.013), with weak correlation strength. A significant positive relationship observed between neuroticism and burnout (r = 0.37; p = 0.003) with weak-to-moderate correlation. Extraversion, agreeableness, openness to experience did not demonstrate significant relationships with bumout (p > 0.05). These findings suggest that personality characteristics influence employee burnout levels and may inform strategies to prevent and manage burnout in healthcare settings. The study may serve as a reference for developing national-level mental health initiatives for public health center employees. Keywords: Big Five Personality Traits, burnout, public health center employees